DOP68 Assessment of patients' understanding of Inflammatory Bowel Diseases (IBD): Development and validation of a questionnaire (U-IBDQ). (27th May 2021) - Ostromohov, G; Fiebelman, M; Hirsch, A; Ron, Y; Aviv Cohen, N; Kariv, R; Deutsch, L; Anbar, R; Maharshak, N; Fliss Isakov, N
Abstract: Background: Education of inflammatory bowel disease (IBD) patients regarding their disease, therapeutic aims and options, is important for patients' empowerment and commitment to disease management. Currently, there is no standardized and validated tool for assessment patients' knowledge of their disease. Therefore, we aimed to develop a questionnaire to evaluate IBD patients' understanding of disease pathophysiology and treatment. Methods: We have developed the Understanding IBD Questionnaires (U-IBDQ), consisting of multiple-choice questions in two version [for Crohn's disease (CD) and ulcerative colitis (UC)]. U-The U-IBDQ is composed of 36 questions covering 8 IBD topics. Each question received a similar weight, and total score ranges between 0–100. Questionnaires were tested for: content validity by an independent multidisciplinary stirring committee using the content validity index, face validity, readability and responsiveness on a pilot group of IBD patients. Convergent validity was assessed by correlating scores of the U-IBDQ with physician's subjective assessment of disease understanding and knowledge. Discriminant validity was assessed by comparison to healthy controls (HC), patients with chronic gastrointestinal (GI) conditions other than IBD, and to GI nurses. A test-retest reliability was assessed among a sub-population of IBD patients which were asked to fill-in the U-IBDQ twice. Multivariate analysis was used to determine associated factors of a high level of disease understanding. Results: Study population consisted of IBD patients (n=106), HC (n=35), chronic GI disease patients (n=38) and GI nurses (n=19). Mean U-IBDQ score among IBD patients was 56.5±21.9, not differing between CD and UC patients (P=0.941). There was a strong correlation between the U-IBDQ score and the physician's subjective score (r=0.747, P<0.001). The U-IBDQ showed strong discriminant validity with mean score of IBD patients significantly higher than that of HC and chronic GI disease patients, and was lower than that of GI nurses (P<0.001). The U-IBDQ is reliable as determined by Cronbach's alpha = 0.872. Independent factors associated with high U-IBDQ scores included academic education (OR=1.21, 95% CI 1.10–1.33, P<0.001), biologic therapy experience (OR=1.24, 95% CI 1.01–1.53, P=0.046), and IBD diagnosis before the age of 21 years (OR=2.97, 95% CI 1.05–8.87, P=0.050). Conclusion: We have developed and meticulously validated the U-IBDQ. This is a short, self-report questionnaire that has demonstrated good reliability and validity in measuring understanding of disease pathophysiology and treatment in IBD.